Melanoma differentiation‐associated gene 5 in zebrafish provoking higher interferon‐promoter activity through signalling enhancing of its shorter splicing variant. Issue 2 (February 2014) - Zou, Peng Fei; Chang, Ming Xian; Xue, Na Na; Liu, Xue Qin; Li, Jun Hua; Fu, Jian Ping; Chen, Shan Nan; Nie, Pin
Summary Melanoma differentiation‐associated gene 5 (MDA5) is one of the three members in the retinoic acid‐inducible gene I‐like receptor (RLR) family, which are cytoplasmic pathogen recognition receptors recognizing intracellular viruses. In the present study, MDA5 and its spliced shorter forms, named as MDA5a and MDA5b, were identified in zebrafish. MDA5a and MDA5b can be up‐regulated in cell lines following the infection of a negative ssRNA virus, the spring viraemia of carp virus (SVCV), and an intracellular Gram‐negative bacterial pathogen Edwardsiella tarda, implying that the RLR may also be able to sense elements released from bacteria. The over‐expression of MDA5a and MDA5b in fish cells resulted in significant induction of type I interferon promoter activity and enabled the protection of transfected cells against SVCV infection. Furthermore, the shorter spliced form, MDA5b when co‐transfected with MDA5a or mitochondrial antiviral signalling protein (MAVS), induced a significantly higher level of interferon promoter activity, indicating that MDA5b may function as an enhancer in the interaction between MDA5 and MAVS.